A Theory‐Driven Investigation of the Association Between Emotion Dysregulation and Suicide Risk in a Clinical Adolescent Sample. Issue 4 (10th May 2018) - Eaddy, Michael; Zullo, Lucas; Horton, Sarah E.; Hughes, Jennifer L.; Kennard, Betsy; Diederich, Andrew; Emslie, Graham J.; Schuster, Lisa; Stewart, Sunita M.
Abstract : Objective: Emotion dysregulation has been consistently linked to suicide ideation and attempt, but an explanatory model for this relationship has not been adequately investigated in adolescents. This study examined the concurrent relationship among emotion dysregulation, variables from the Interpersonal–Psychological Theory of Suicide (IPTS), and suicide risk (operationalized as a continuous variable that increases in intensity from nonspecific to active suicide ideation to suicide ideation with a plan) in a clinical adolescent sample. Method: A total of 151 adolescents (aged 12–17) were recruited from an inpatient psychiatry unit. Cross‐sectional analyses were conducted to determine whether the relationship between emotion dysregulation and suicide risk was explained by the variables of perceived burdensomeness (PB), thwarted belongingness, and capability for suicide, as proposed by the IPTS. Results: As hypothesized, the relationship between emotion dysregulation and suicide risk was explained by PB and capability for suicide. Depressive symptoms had an independent relationship with suicide risk after controlling for IPTS variables. Conclusions: The results from this study suggest that effective treatment strategies that reduce negative cognition tied to PB and depressive symptoms would address the most proximal variables related to suicide risk in adolescents. Enhancing emotion management would serve to maintain low levels of proximal influences on risk.